2017
DOI: 10.1101/195768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How genetic disease risks can be misestimated across global populations

Abstract: Background: Accurate assessment of health disparities requires unbiased knowledge of genetic risks in different populations. Unfortunately, most genome-wide association studies use genotyping arrays and European samples. Here, we integrate whole genome sequence data from global populations, results from thousands of GWAS, and extensive computer simulations to identify how genetic disease risks can be misestimated.Results: In contrast to null expectations, we find that risk allele frequencies at known disease l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Therefore, an allele that is rare in the GWAS sample but common elsewhere will not be discovered, leading to a greater reduction in the variance accounted for, or prediction accuracy, in non-represented populations. (Liu et al, 2015;Martin et al, 2017a,b;Curtis, 2018;Kim et al, 2018;Bentley et al, 2019;Wojcik et al, 2019;Wang et al, 2020;Conti et al, 2021;Cavazos and Witte, 2021). The impact of genetic differentiation on prediction accuracy in non-represented populations can be large, as it has been found that many variants contributing to trait variation in European GWAS samples were not at a high enough frequency to be detected in other populations, suggesting different alleles contribute greatly to the trait variance in each population (Liu et al, 2015;Durvasula and Lohmueller, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an allele that is rare in the GWAS sample but common elsewhere will not be discovered, leading to a greater reduction in the variance accounted for, or prediction accuracy, in non-represented populations. (Liu et al, 2015;Martin et al, 2017a,b;Curtis, 2018;Kim et al, 2018;Bentley et al, 2019;Wojcik et al, 2019;Wang et al, 2020;Conti et al, 2021;Cavazos and Witte, 2021). The impact of genetic differentiation on prediction accuracy in non-represented populations can be large, as it has been found that many variants contributing to trait variation in European GWAS samples were not at a high enough frequency to be detected in other populations, suggesting different alleles contribute greatly to the trait variance in each population (Liu et al, 2015;Durvasula and Lohmueller, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Even with perfectly estimated effects at the causal loci with significant trait associations, the prediction accuracy of polygenic scores will be limited because GWAS only identify loci with common alleles that contribute enough variance to exceed some significance threshold determined by the sample size. Therefore, an allele that is rare in the GWAS sample but common elsewhere will not be discovered, leading to a greater reduction in the variance accounted for, or prediction accuracy, in unrepresented populations (Martin et al ., 2017a,b; Curtis, 2018; Kim et al ., 2018; Bentley et al ., 2019; Wojcik et al ., 2019; Wang et al ., 2020; Conti et al ., 2021). Indeed, many variants contributing to trait variation in European GWAS samples are not at a high enough frequency to be detected in other populations, suggesting different sets of polymorphisms contribute to the trait variance in different populations (Liu et al ., 2015; Durvasula and Lohmueller, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an allele that is rare in the GWAS sample but common elsewhere will not be discovered. This would lead to a greater reduction in the phenotypic variance accounted for, or prediction accuracy, in populations not represented in the GWAS sample (hereafter 'unrepresented populations'; [30,40,44,[48][49][50][51][52]). Indeed, many variants contributing to trait variation in European GWAS samples are not at a high enough frequency to be detected in other populations, suggesting that different sets of polymorphisms contribute to the trait variance in different populations [53,54].…”
Section: Introductionmentioning
confidence: 99%